2014
DOI: 10.3892/mco.2014.443
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of thymidylate synthase expression in pancreatic adenocarcinoma: A meta-analysis

Abstract: The prognostic significance of thymidylate synthase (TS) overexpression in pancreatic adenocarcinoma has been extensively investigated; however, data on the survival of patients with pancreatic adenocarcinoma remain equivocal. We performed a meta-analysis of previous studies to assess the effects of TS overexpression on the overall survival (OS) of patients with pancreatic adenocarcinoma, using hazard ratio (HR) with its 95% confidence interval (CI). A total of 5 studies, including 425 patients, were subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…We demonstrated the predictive value of this protein in 2 separate patient cohorts who received different therapies. Additionally, we incorporated 2 known biomarkers for pancreatic cancer, DPC4 (3, 4) and TS (10, 11), to create a multi-protein predictor of distant metastasis in patients receiving multimodality therapy. The predictor divided our patient population in approximately half.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated the predictive value of this protein in 2 separate patient cohorts who received different therapies. Additionally, we incorporated 2 known biomarkers for pancreatic cancer, DPC4 (3, 4) and TS (10, 11), to create a multi-protein predictor of distant metastasis in patients receiving multimodality therapy. The predictor divided our patient population in approximately half.…”
Section: Discussionmentioning
confidence: 99%
“…In pancreatic cancer, a study by Hu et al (10) found that high TS expression was associated with poorer survival in patients who underwent surgery. In contrast, smaller studies examining the prognostic utility of TS in pancreatic cancer have demonstrated conflicting results (11).…”
Section: Introductionmentioning
confidence: 99%